Fascialage: A Refined Technique of Dorsal Augmentation in Rhinoplasty - Prashantha Kesari; Sameer Halageri; Pradeep Kumar (Indian Journal of Plastic Surgery, 2025)
Introduction The primary aim of this paper is to describe an original technique for dorsal augmentation in rhinoplasty. The use of a carved block of costal cartilage or layers of septal cartilage is a well-known technique for dorsal augmentation. However, this is accompanied by the risks of cartilage warping and a hard, unnatural feel to the dorsum. On the other hand, the use of diced cartilage wrapped in the fascia, which has been another popular technique in the last decade, often does not give the structural stability of a solid cartilage. “Fascialage,” as innovated by the authors, is a combined construct that incorporates all the advantages of these techniques eliminates the disadvantages of the previous techniques.